Dietary and pharmacological intervention to mitigate the cardiopulmonary effects of air pollution toxicity - Tong, Haiyan (Biochimica et biophysica acta, 2016)
Exposure to air pollution contributes importantly to excess morbidity and mortality. And while regulatory actions under the “Clean Air Act” have saved millions of lives by improving air quality, there are still millions of people in the U.S. who live in areas where particulate air pollution (PM) levels exceed the U.S. Environmental Protection Agency's National Ambient Air Quality Standards. Therefore, apart from such localities working to attain such standards the protection of the health of public and in particular those at high risk might benefit from interventional strategies that would ameliorate air pollution's adverse health effects. Because inflammation and oxidative stress appear to mediate the health effects of air pollution, one interventional approach to consider is the use of dietary supplementation or medication with anti-inflammatory or antioxidant properties to block the biological responses that initiate the pathophysiological process that culminates in adverse health effects. This article reviews the capability of dietary supplementation, such as antioxidant vitamins, polyunsaturated fatty acids, and medications as a strategy to mitigate air pollution-induced subclinical cardiopulmonary effects. Antioxidant vitamins C and E protect the lungs against short-term ozone and PM exposure. Polyunsaturated fatty acids, such as fish oil and olive oil appear to offer protection against short-term air pollution-induced adverse cardiovascular responses. Taking dietary supplements or medications with antioxidant or anti-inflammatory properties has the potential to provide at least partial protection against air pollution-induced adverse health effects in those individuals who are known to be most susceptible, namely those with pre-existing respiratory and cardiovascular diseases. This article is part of a Special Issue entitled Air Pollution, edited by Wenjun Ding, Andrew J. Ghio and Weidong Wu. •Antioxidant vitamins protect the lungs against air pollution.•Polyunsaturated fatty acids appear to protect the cardiovascular system against air pollution.